Implementation of Fuzzy C-Means Algorithm with Lossy Method for Sasirangan Image Compression - Qur’ana, Tri Wahyu; M. Dedy Rosyadi (Tinta Emas Publisher, 2024)
Sasirangan as the Banjar people's creative work is a typical icon of South Kalimantan and Widely known for its patterns and uniqueness which highly demanded by local, national and foreign people. Sasirangan textile marketing using the marketplace, Sasirangan image with patterns of different colours have large storage capacity, as well as uploading images of Sasirangan patterns in e-commerce requires large bandwidth, while the constraints on MSME entrepreneurs have limited Internet bandwidth access. Image compression aims to convert data files into smaller files for efficient storage and effective data transmission. The vector quantization method is a mapping of image data in the form of irregular bits, so the mapping uses the fuzzy C-mean algorithm. The achieved compression kulat kurikit.jpg is higher than that of other images, with a compression ratio of 88.5233600% and a file size of 566 KB. a better quality than the others due to its more uniform grey scale colour composition for the same block vector and codebook.